Osteopontin deletion drives hematopoietic stem cell mobilization to the liver and increases hepatic iron contributing to alcoholic liver disease - Magdaleno, Fernando (Hepatol Commun, 2017)
The aim of this study was to investigate the role of osteopontin (OPN) in hematopoietic stem cell (HPSC) mobilization to the liver and its contribution to alcoholic liver disease (ALD). We analyzed young (14‐16 weeks) and old (>1.5 years) wild‐type (WT) littermates and global Opn knockout (Opn(−/−)) mice for HPSC mobilization to the liver. In addition, WT and Opn(−/−) mice were chronically fed the Lieber–DeCarli diet for 7 weeks. Bone marrow (BM), blood, spleen, and liver were analyzed by flow cytometry for HPSC progenitors and polymorphonuclear neutrophils (PMNs). Chemokines, growth factors, and cytokines were measured in serum and liver. Prussian blue staining for iron deposits and naphthol AS‐D chloroacetate esterase staining for PMNs were performed on liver sections. Hematopoietic progenitors were lower in liver and BM of young compared to old Opn(−/−) mice. Granulocyte colony‐stimulating factor and macrophage colony‐stimulating factor were increased in Opn(−/−) mice, suggesting potential migration of HPSCs from the BM to the liver. Furthermore, ethanol‐fed Opn(−/−) mice showed significant hepatic PMN infiltration and hemosiderin compared to WT mice. As a result, ethanol feeding caused greater liver injury in Opn(−/−) compared to WT mice. Conclusion: Opn deletion promotes HPSC mobilization, PMN infiltration, and iron deposits in the liver and thereby enhances the severity of ALD. The age‐associated contribution of OPN to HPSC mobilization to the liver, the prevalence of PMNs, and accumulation of hepatic iron, which potentiates oxidant stress, reveal novel signaling mechanisms that could be targeted for therapeutic benefit in patients with ALD. (Hepatology Communications 2018;2:84–98)